2008
DOI: 10.1161/strokeaha.107.502229
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling the Brain

Abstract: Background and Purpose-Studies on adult stroke patients have demonstrated functional changes in cortical excitability, metabolic rate, or blood flow after motor therapy, measures that can fluctuate rapidly over time. This study evaluated whether evidence could also be found for structural brain changes during an efficacious rehabilitation program. Methods-Chronic stroke patients were randomly assigned to receive either constraint-induced movement therapy (nϭ16) or a comparison therapy (nϭ20). Longitudinal voxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
151
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(164 citation statements)
references
References 32 publications
(41 reference statements)
6
151
2
3
Order By: Relevance
“…Constraint-induced movement therapy (CIMT) is an intervention for patients with hemiplegia in which they wear a restraining mitt on the less-affected hand while engaging in repetitive task practice and behavioral shaping with the hemiplegic hand [Gauthier et al, 2008]. The EXCITE (Effect of Constraint-Induced Movement Therapy on Upper Extremity Function) randomized clinical trial of this therapy in adults with stroke in the previous 6-9 months showed that it produced significant and clinically relevant improvement in arm motion that persisted for at least 1 year [Wolf et al, 2007].…”
Section: Structural Neuroplasticity After Therapy For Hemiparesismentioning
confidence: 99%
See 1 more Smart Citation
“…Constraint-induced movement therapy (CIMT) is an intervention for patients with hemiplegia in which they wear a restraining mitt on the less-affected hand while engaging in repetitive task practice and behavioral shaping with the hemiplegic hand [Gauthier et al, 2008]. The EXCITE (Effect of Constraint-Induced Movement Therapy on Upper Extremity Function) randomized clinical trial of this therapy in adults with stroke in the previous 6-9 months showed that it produced significant and clinically relevant improvement in arm motion that persisted for at least 1 year [Wolf et al, 2007].…”
Section: Structural Neuroplasticity After Therapy For Hemiparesismentioning
confidence: 99%
“…The EXCITE (Effect of Constraint-Induced Movement Therapy on Upper Extremity Function) randomized clinical trial of this therapy in adults with stroke in the previous 6-9 months showed that it produced significant and clinically relevant improvement in arm motion that persisted for at least 1 year [Wolf et al, 2007]. The effect of this technique on structural plasticity in the brain has been examined using voxelbased morphometry in a group of 49 patients (26 male, 23 female) with an average age of 65 years who were an average of 3.6 years out from a stroke and had mild to moderate upper extremity hemiparesis [Gauthier et al, 2008]. Patients randomized to the CIMT therapy received 3 hr of therapy for the hemiparetic arm daily for 10 consecutive weekdays and restraint of the less-impaired arm for a target of 90% of waking hours.…”
Section: Structural Neuroplasticity After Therapy For Hemiparesismentioning
confidence: 99%
“…Foram encontrados 352 artigos, dos quais apenas 6 (27)(28)(29)(30)(31)(32) a) há poucos artigos que comparam a TCI com outra técnica de reabilitação; b) dentre os artigos encontrados, com exceção do estudo EXCITE, o número da amostra é pequeno; e c) os artigos somente foram pesquisados em três bases de dados.…”
Section: Resultsunclassified
“…For example, studies of post-stroke therapies demonstrate both restoration of functional organization and creation of neuronal projections [45][46][47] while similar studies of brain or spinal cord injuries correlate clinical improvement with observable changes in functional and structural neuroimaging. 48,49) There has been increasing interest in the possibility of involving neuroplasticity in the treatment of psychiatric disorders. Just as physical rehabilitation in the setting of trauma to the nervous system leads to functional improvement of the motor system, cognitive training is being developed across a variety of clinical conditions, from neurodevelopmental disorders 50) to aging 51) to neuropsychiatric illnesses, including schizophrenia.…”
Section: Neuroplasticity As a Therapeutic Target In Schizophreniamentioning
confidence: 99%